Policy experiments failures and innovations beyond accession in Central and Eastern Europe - edited by Agnes Batory (Cheltenham Edward Elgar Pub, 2018)
Policy Experiments, Failures and Innovations takes a policy studies perspective in considering post-communist EU member states’ experiences since accession. The book analyses policy transfer processes and expands the new and growing sub-field of policy failure by interrogating the binary ideas of ‘failure’ and ‘success’ in the context of the Central Eastern European (CEE) transition, democratic consolidation and European Union membership.
Includes bibliographical references and index.
Keywords: European Union -- Europe, Central